Effects of sea depths and sizes of winged pearl oysters (Pteria penguin) on pearl culture - Inthonjaroen, N.; Piyathamrongrut, K.; Kanjanachatree, K. (Songklanakarin Journal of Science and Technology (SJST), 2003)
Environmental aspects and biology of pearl oysters are the important conditions affecting pearl production. In order to obtain commercially valuable pearl from winged pearl oysters, Pteria penguin, three sizes (shell-length) of the oysters: small (130-135 mm), medium (160-165 mm) and large (185-200 mm) were suspended at 2 m (surface), 5 m (mid-depth) and 8 m (bottom) below the sea surface from February to November, 2001. Using a factorial design, the data were randomly recorded by month. All sizes of the pearl oysters at the surface produced pearl of significantly greater thickness than those at the greater depths. The small-sized pearl oysters at the surface depth produced the thickest pearl (0.612 mm.) which took only 7 months for harvesting, and the pearl thickness was correlated with growth response in shell length. In contrast to the growth rate in tissue weight and mortality rates which were 36.00, 26.00, 24.00% at the surface depth; 30.60, 24.60, 16.00% at mid-depth and 25.30, 19.30, 12.00% at the bottom for the small, medium and large-sized oysters, respectively. The results depended on infestation of fouling organisms on oyster shells which were much more intense at the surface than at a greater depths and slowed the growth rate in tissue weight, especially in the small-sized oysters. However, there was a greater amount of many kinds of plankton, the food resource of marine animals, at surface than at greater depths, so it retained shell-length growth and pearl production of the small-sized oysters: The other environmental factors, such as salinity, dissolved oxygen, pH and sea water temperature, at all depths did not have an impact on the pearl oyster rearing.